Application of Euler Method on Ice Sheet Buckling - Koto, J; Afrizal, Efi; M.A, Wahid (Journal of Ocean, Mechanical and Aerospace -science and engineering-, 2018)
Bulbous bow ship economically has advantage during sailing in open water due to lower resistance compared with an ice bow. On the other hand, the movement of the ship gradually give load to the ice sheet, along with that, the ice sheet will react in proportion to the load of the ship. Therefore the bulbous bow ship has higher ice resistance. This paper discusses the phenomena of ice sheet buckling due bulbous bow of ice ship. The ice sheet buckling was analyzed using Finite Element Method based on Euler method. The Euler method was described from general deflection equation for a beam.